2013
DOI: 10.1177/2048872613484687
|View full text |Cite
|
Sign up to set email alerts
|

Venous-arterial extracorporeal membrane oxygenation for refractory cardiac arrest: a clinical challenge

Abstract: Guidelines stated that extracorporeal membrane oxygenation (ECMO) may improve outcomes after refractory cardiac arrest (CA) in cases of cardiogenic shock and witnessed arrest, where there is an underlying circulatory disease amenable to immediate corrective intervention. Due to the lack of randomized trials, available data are supported by small series and observational studies, being therefore characterized by heterogeneity and controversial results. In clinical practice, using ECMO involves quite a challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 37 publications
0
49
0
1
Order By: Relevance
“…They also found that a shorter period between CPR initiation and ECMO commencement resulted in better chance of successful weaning off ECMO (p=0.006), and that earlier weaning from ECMO yielded better outcomes. Lazzeri and colleagues' systematic review also found that outcomes depend heavily on the expertise of ECMO team [9]. The analysis revealed that ECMO patients were significantly more likely to develop ARF than non-ECMO patients (36% vs. 8%, p<.05), especially if the ECMO was emergently instituted.…”
Section: Page 9 Of 19mentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that a shorter period between CPR initiation and ECMO commencement resulted in better chance of successful weaning off ECMO (p=0.006), and that earlier weaning from ECMO yielded better outcomes. Lazzeri and colleagues' systematic review also found that outcomes depend heavily on the expertise of ECMO team [9]. The analysis revealed that ECMO patients were significantly more likely to develop ARF than non-ECMO patients (36% vs. 8%, p<.05), especially if the ECMO was emergently instituted.…”
Section: Page 9 Of 19mentioning
confidence: 99%
“…A 2013 systematic review of ECMO in the context of refractory cardiac arrest concluded that in-hospital survival rates vary greatly from 6-59%, largely due to differences in patient selection [9]. Recently Kim and colleagues retrospectively reviewed 27 patients that required rescue ECMO for acute myocardial infarction complicated by cardiogenic shock: 82% of these patients were successfully weaned off ECMO, and 59% survived to discharge [10].…”
Section: Page 9 Of 19mentioning
confidence: 99%
“…ECMO is an external device that supports the cardiopulmonary system by providing oxygenation and cardiac function for a patient in cardiac and respiratory failure. ECMO has been successfully used in all ages for various medical and surgical conditions leading to cardiovascular collapse, respiratory failure, cardiogenic shock, or refractory hypotension [2][3][4][5][6][7][8][9]. ECMO has also been used in poisoning exposures when cardiac arrest or refractory hypotension develops.…”
Section: Introductionmentioning
confidence: 99%
“…Such information is needed to inform potential consensus guidelines for patient selection and to allow meaningful meta-analyses. It could also help explain some apparent inconsistencies in outcome predictors that in this study did not include cardiac arrest variables, age, and lactate as reported earlier [7][8][9], albeit not specifically in patients with cardiogenic shock following cardiac arrest.…”
mentioning
confidence: 78%
“…The 2013 ELSO Guideline lists prolonged cardiopulmonary resuscitation without adequate tissue perfusion as an absolute contraindication to VA-ECMO but the lack of detail makes this statement difficult to implement. Published case series suggest that time to commencing VA-ECMO is critical to its success and should be limited to 30-60 min after cardiac arrest [7,8] whereas age, an independent predictor of in-hospital mortality, is arbitrarily defined [9]. Furthermore, while ECMO pump devices, tubing and cannulation procedures are becoming increasingly sophisticated and more compact mobile systems are available [10], the use of VA-ECMO is still associated with significant morbidity [11].…”
mentioning
confidence: 99%